Balanço hídrico em bacia urbana - Dalla Corte, Ariéli Corrêa (2015)
This work aims to study the behavior of the variables precipitation, evapotranspiration, runoff and water storage in the soil, involved in water balance of the arroio Cancela basin, in Santa Maria, RS. The monitoring was conducted from 02 May to 07 november of 2014. The measurement of volumetric water content in the soil to the water balance was made priority every 7 days, with TDR probe at average depths of 20, 40, 60 and 80 cm, in access tubes installed until 1,0 m of depth in three sites on the basin: CACISM (53°48 1,41‖ W e 29º42 5,5‖S), Cerrito (53º47 21,9‖ W e 29º42 7,2‖ S) e DAER (53º48 9,4‖W e 29º41 38,5‖ S). In the period from 12 to 26 june was measured soil moisture content daily to observe the behavior of this variable between two rain events. Rainfall was monitored from rain gauges installed in points Cerrito and DAER. The runoff was obtained with level recorder installed at river section of CACISM site using a existing rating curve and evapotranspiration was calculated by Penman-Monteith-FAO method using data colected through data measured in meteorological station installed at this point and others purchased from the National Institute of Meteorology network (INMET), from weather stations installed on the campus of the Federal University of Santa Maria (UFSM). The monthly precipitation was higher for the month of June and lowest for the month of August. Evapotranspiration was growing between the months from june to october and its behavior over the period was justified by the change in climatic factors. The variation of the run off accompanied with the variation of rainfall 0.9519 correlation between variables. The influence of precipitation on the water content was confirmed in the daily measurements in the fortnight. Variations of textural characteristics to the soil types of the sites are the factor that best explains the soil moisture behavior in profiles. The textural variations are the factor that better explains the soil moisture behavior in profiles. The water balance of the basin for the period studied shows greater variations (excess of water) near the beginning of winter, in the period between 19 june to 03 july and near the beginning of spring, between 29 august and 16 september. In august had the highest water deficit.